Anaerobic Digester Installation Significantly Reduces Liquid Manure Management CH4 Emissions at a California Dairy Farm - Michael V. Rodriguez; Nidia Rojas Robles; Valerie Carranza; Ranga Thiruvenkatachari; Mariana Reyes; Chelsea V. Preble; Joyce Pexton; Deanne Meyer; Ray G. Anderson; Akula Venkatram; Francesca M. Hopkins (GCB Bioenergy, 2025)
ABSTRACT Anaerobic digesters are expected to significantly reduce CH4 emissions from dairy manure management by capturing them for use as biogas. Anaerobic digestion is the current major mitigation strategy for agricultural CH4 emissions in California's climate policy. However, verification of the effectiveness of anaerobic digesters to reduce CH4 emissions has not been conducted at scale in California. We made atmospheric measurements from a mobile platform and used dispersion modeling to estimate CH4 emissions from a liquid manure storage complex at a typical California dairy before and after digester installation across nine field campaigns. The anaerobic digester reduced CH4 emissions by an average of 82% ± 16%, comparing paired months to predigester values. Prior to the digester, atmospheric CH4 mole fractions showed a persistent hotspot near the manure settling basin cells of 28.6 ± 8.9 ppm. After the digester, atmospheric CH4 mole fractions from manure storage were greatly reduced. We observed strong temporal variability across measurement campaigns due to weather, on‐farm management practices, and digester operations. Estimated emissions greatly exceeded those based on inventory calculations used by the California Air Resources Board (CARB) but were in line with expected relative emissions reduction from digester installation. Scaling these results to 139 dairies with digester projects statewide suggests that similarly operating digesters would reduce CH4 emissions by 1.6 ± 0.3 MMT CO2e (65 ± 12 Gg CH4), 39% of the emissions reduction goal for livestock manure management set by California law. This work demonstrates the effectiveness of anaerobic digesters to reduce dairy manure management CH4 emissions in practice, along with the importance of understanding operations and management for interpreting on‐farm CH4 emissions studies.